2017
DOI: 10.18203/issn.2454-2156.intjscirep20174867
|View full text |Cite
|
Sign up to set email alerts
|

Screening for congenital hypothyroidism: results of screening 5600 Ardabil province infants

Abstract: <p class="abstract"><strong>Background:</strong> Congenital hypothyroidism (CH) is a condition of thyroid hormone deficiency which varies more by geographic areas and affecting 1 in 3000 to 4000 of newborns. The aim of this study was to investigate the screening of CH results in in Ardabil Province, Iran.</p><p class="abstract"><strong>Methods:</strong> This descriptive study was conducted on 158624 neonates during 2007 to 2013 which were screened for CH by measuring s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…13 There are some variations in different areas of Iran; for instance, in Tehran, Isfahan, Markazi province and Yazd (central cities of the country), the average prevalence rates of CH are reported at 1:914, 1:338, 1:307 and 1:1608 live births, respectively. 13,21,22 The incidence of CH in Ardabil was found to be 1:916, 23 whereas in the north of Iran, it was estimated at 1 per 491 live births. 24 Nevertheless, the prevalence of CH in Iran is higher than other countries.…”
Section: Discussionmentioning
confidence: 99%
“…13 There are some variations in different areas of Iran; for instance, in Tehran, Isfahan, Markazi province and Yazd (central cities of the country), the average prevalence rates of CH are reported at 1:914, 1:338, 1:307 and 1:1608 live births, respectively. 13,21,22 The incidence of CH in Ardabil was found to be 1:916, 23 whereas in the north of Iran, it was estimated at 1 per 491 live births. 24 Nevertheless, the prevalence of CH in Iran is higher than other countries.…”
Section: Discussionmentioning
confidence: 99%
“…2 In the study conducted by Mirzarahimi and colleagues in Ardabil province on 160 babies, they showed that the prevalence of permanent hypothyroidism in Ardabil province was 1 in 4000. 3 Considering the complications of this disease and the importance of its timely diagnosis and treatment for babies up to 6 weeks old, screening for congenital thyroid disease is done from the heel and suspicious cases are diagnosed and treated. If the baby's TSH is above 20, hypothyroidism is considered and treated.…”
Section: Introductionmentioning
confidence: 99%